INFLUENCE OF RUN AND CUT MANOEUVRES ON PATELLOFEMORAL KINETICS AND KINEMATICS. Issue 22 (1st November 2016) - Sinclair, J; Dillon, S
Abstract : Patellofemoral pain syndrome is the most common knee pathology. Those with patellofemoral pain are much more likely to be physically active than age-matched controls. The prevalence of patellofemoral pain in athletic populations is considered to be between 8–40 %. It has been suggested that patellofemoral pain may serve as a precursor to the progression of osteoarthritic symptoms in later life. The effects of different sports tasks on patellofemoral kinetics and kinematics has received a paucity of research attention. The aim of the current investigation was to explore differences in patellofemoral kinetics and kinematics during the run and cut manoeuvres. Ten male participants took part in this investigation. They performed run and 45˚ cut movements using an approach velocity of 4.0 m.s −1 . Three-dimensional kinematics of the thigh, shank and patella segments were quantified using retro reflective markers via an eight camera motion capture system which operated at 250 Hz. In addition to this patellofemoral kinetics were quantified using a musculoskeletal modelling approach. Differences between manoeuvres were explored statistically using paired samples t-tests. The results showed that patellofemoral force (Cut=4.65 & Run=4.11 Bodyweights) and pressure (Cut=12.32 & Run=10.93 MPa) were larger in the cut movement compared to the run. In addition patella angular range of motion was larger in the sagittal (Cut=11.66 & Run=7.89°) and transverse (Cut=13.55 & Run=7.57°) planes when performing the cut movement in comparison to the run. In conclusion given the association between patellofemoral loading/ patella mal-alignment and the aetiology of patellofemoral pain syndrome, the current study indicates that the cut manoeuvre may place athletes at increased risk from injury.